PENILAIAN TINGKAT KEBAHAGIAAN MASYARAKAT KAMPUNG KOTA (STUDI KASUS KAWASAN PERMUKIMAN KAMPUNG BRAGA BANDUNG) - Sally Indah Nurdyawati; Holi Bina Wijaya (Diponegoro University, 2018)
The measurement of happiness index in Indonesia was conducted by Badan Pusat Statistik (BPS) was first released in 2013 based on the result of study and representation of national level estimation. The approach taken is a life satisfaction, in which life satisfaction is believed to reflect the level of happiness. The city of Bandung is one of the cities that initiated the measurement of happiness index in Indonesia. Kampung Braga is one of Kampung Kota that still maintain its existence in the middle of the urban development. The neighborhood of Kampung Braga is considered as slum area and the buildings within break the river border line. According to than phenomena, the research question comes up,